Health system and patient-level factors associated with multidisciplinary care and patient education among hospitalized, older cancer survivors - Rachelle Brick; Daniel J. Hekman; Nicole E. Werner; Juleen Rodakowski; Lisa Cadmus-Bertram; Beth Fields (Elsevier, 2023)
Objective: The purpose of this study was to examine system- and patient-level factors associated with the number of healthcare disciplines involved in delivery of patient education among hospitalized older cancer survivors. Methods: We used electronic health record (EHR) data from a single institution documenting patient education among hospitalized older patients (≥65 years) with a history of cancer between 9/1/2018 and 10/1/2019. We used parametric ordinal logistic regression to assess the number of healthcare disciplines involved in documented education activities. Results: The sample (n = 446) was predominantly male, White, and on average 74 years old. Adjusting for patient and system-level variables, men and larger department units had higher odds of receiving education from fewer healthcare disciplines. Patients with a history of breast or prostate cancer and longer lenths of stay had lower odds of receiving patient education from fewer healthcare disciplines. Conclusion: Hospital size, severity of illness, and cancer type are associated with delivery of multidisciplinary education in this sample. Innovation: EHR provides an opportunity to identify patterns in patient education among cancer survivors. Future research should investigate provider perspectives of the findings to inform provider- and system-level strategies to improve patient education.